Determinants of spatial distribution of trees outside forests along urban-rural gradients: A review - Dorcas Wambui Kariuki; Sammy C. Letema; Godwin O. Opinde (Sustinere: Journal of Environment and Sustainability, 2024)
Urbanization can create uncertainty for biodiversity. Understanding the spatial distribution of trees along urban-rural gradients is crucial for sustainable land management and the conservation of biological diversity. However, limited information is available on the factors influencing the distribution of trees outside forests along urban-rural transition gradients. This paper uses the Preferred Reporting items for Systematic Reviews and Meta-Analyses (PRISMA) to review how distance from urban centers, land use types, socio-economic disparities, and community attitudes and perceptions impact the spatial distribution of trees outside forests along urban-rural gradients. The review indicates that the species composition, diversity, density, and spatial arrangement of trees outside forests vary along the urban-rural gradient. The most commonly cited factors influencing this distribution are respondents' attitudes and perceptions of trees, socio-economic factors, and land use variations. Distance from the urban center was the least cited factor. However, there is significant variation in how different factors impact this distribution from study to study. Therefore, further research is needed to better understand the factors driving changes in the diversity of trees outside forests in various urban-rural contexts and to determine whether variations exist across different settings.